Influence of SOS-inducing agents on the expression of ArtAB toxin gene in Salmonella enterica and Salmonella bongori. Issue 8 (24th August 2020) - Miura, Shou; Tamamura, Yukino; Takayasu, Mariko; Sasaki, Miwa; Nishimura, Natsuko; Tokugawa, Kanetaka; Suwa, Izumi; Murata, Ryo; Akiba, Masato; Kusumoto, Masahiro; Uchida, Ikuo
Abstract : Salmonella enterica subspecies enterica serovar Typhimurium ( S . Typhimurium) definitive phage type 104 (DT104), S. enterica subspecies enterica serovar Worthington ( S . Worthington) and S. bongori produce ArtA and ArtB (ArtAB) toxin homologues, which catalyse ADP-ribosylation of pertussis toxin-sensitive G protein. ArtAB gene ( artAB ) is encoded on prophage in DT104 and its expression is induced by mitomycin C (MTC) and hydrogen peroxide (H2 O2 ) that trigger the bacterial SOS response. Although the genetic regulatory mechanism associated with artAB expression is not characterized, it is thought to be associated with prophage induction, which occurs when the RecA-mediated SOS response is triggered. Here we show that subinhibitory concentration of quinolone antibiotics that are SOS-inducing agents, also induce ArtAB production in these Salmonella strains. Both MTC and fluoroquinolone antibiotics such as enrofloxacin-induced artA and recA transcription and artAB -encoding prophage (ArtAB-prophage) in DT104 and S . Worthington. However, in S. bongori, which harbours artAB genes on incomplete prophage, artA transcription was induced by MTC and enrofloxacin, but prophage induction was not observed. Taken together, these results suggest that SOS response followed by induction of artAB transcription is essential for ArtAB production. H2 O2 -mediated induction of ArtAB prophage and efficient production of ArtAB was observed in DT104 but not in S . Worthington and S. bongori . Therefore, induction of artAB expression with H2 O2 is strain-specific, and the mode of action of H2 O2 as an SOS-inducing agent might be different from those of MTC and quinolone antibiotics.